2022
DOI: 10.1186/s41021-021-00233-y
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Butadiene: a ubiquitous environmental mutagen and its associations with diseases

Abstract: Abstract1,3-Butadiene (BD) is a petrochemical manufactured in high volumes. It is a human carcinogen and can induce lymphohematopoietic cancers, particularly leukemia, in occupationally-exposed workers. BD is an air pollutant with the major environmental sources being automobile exhaust and tobacco smoke. It is one of the major constituents and is considered the most carcinogenic compound in cigarette smoke. The BD concentrations in urban areas usually vary between 0.01 and 3.3 μg/m3 but can be significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 207 publications
0
28
0
Order By: Relevance
“…106-99-0) for the synthesis of polymers (e.g., synthetic rubber and thermoplastic resins) has led to high demand and large-scale production of BD in the petrochemical industry. , According to the 2016 Chemical Data Reporting (), the annual production volume of BD in the United States was estimated to be between 1 and 5 billion lb (i.e., 0.45 to 2.27 × 10 6 tons). Uncontrolled emission, improper disposal, and accidental spillage have caused the detection of BD in soil, groundwater, surface water, and drinking water supplies, which pose detrimental effects threatening human health . BD has been identified in 17 of the 1867 U.S. Environmental Protection Agency (USEPA) National Priorities List (NPL) sites and is ranked 154 of 857 contaminants in the Substance Priority List .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…106-99-0) for the synthesis of polymers (e.g., synthetic rubber and thermoplastic resins) has led to high demand and large-scale production of BD in the petrochemical industry. , According to the 2016 Chemical Data Reporting (), the annual production volume of BD in the United States was estimated to be between 1 and 5 billion lb (i.e., 0.45 to 2.27 × 10 6 tons). Uncontrolled emission, improper disposal, and accidental spillage have caused the detection of BD in soil, groundwater, surface water, and drinking water supplies, which pose detrimental effects threatening human health . BD has been identified in 17 of the 1867 U.S. Environmental Protection Agency (USEPA) National Priorities List (NPL) sites and is ranked 154 of 857 contaminants in the Substance Priority List .…”
Section: Introductionmentioning
confidence: 99%
“…BD has been identified in 17 of the 1867 U.S. Environmental Protection Agency (USEPA) National Priorities List (NPL) sites and is ranked 154 of 857 contaminants in the Substance Priority List . Toxicological studies have demonstrated that exposure to higher BD concentrations is associated with leukemia and cardiovascular disease and may raise the risks of reproductive illness, cancers, autism, and asthma in children. ,, In 2019, the USEPA designated BD as a high-priority substance for risk evaluation under the Toxic Substances Control Act . To date, comprehensive information regarding the environmental fate of BD (e.g., persistence, degradation, and transformation), particularly under anoxic conditions, is largely lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diepoxybutane (DEB) is the most toxic active metabolite of the environmental chemical 1,3‐butadiene (BD). [ 1 ] BD is a large production volume chemical that is regulated as a hazardous air pollutant. [ 2 ] Human exposure to this compound occurs in occupational settings, and in situations involving fires, automobile exhaust, and cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Human exposure to this compound occurs in occupational settings, and in situations involving fires, automobile exhaust, and cigarette smoke. [ 1,3 ] BD is a known mutagen, carcinogen, genotoxin, and teratogen, and its toxic effects are mediated primarily through its three epoxide metabolites, with DEB being the most potent. [ 1,4–7 ] DEB induces oxidative stress, DNA lesions, protein crosslinks, intra‐strand and interstrand DNA–DNA crosslinks, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%